2021
DOI: 10.1111/jth.15485
|View full text |Cite|
|
Sign up to set email alerts
|

To clot or not to clot? Ad is the question—Insights on mechanisms related to vaccine‐induced thrombotic thrombocytopenia

Abstract: Vaccine‐induced immune thrombotic thrombocytopenia (VITT) has caused global concern. VITT is characterized by thrombosis and thrombocytopenia following COVID‐19 vaccinations with the AstraZeneca ChAdOx1 nCov‐19 and the Janssen Ad26.COV2.S vaccines. Patients present with thrombosis, severe thrombocytopenia developing 5–24 days following first dose of vaccine, with elevated D‐dimer, and PF4 antibodies, signifying platelet activation. As of June 1, 2021, more than 1.93 billion COVID‐19 vaccine doses had been admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 104 publications
0
18
0
1
Order By: Relevance
“…If large immune complexes formed directly with components of the vaccine formulation, then it seems more likely that they would lead to platelet activation and clot formation immediately following vaccination, rather than >5 days later. The discussion surrounding potential mechanisms for TTS has recently been reviewed (9). Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If large immune complexes formed directly with components of the vaccine formulation, then it seems more likely that they would lead to platelet activation and clot formation immediately following vaccination, rather than >5 days later. The discussion surrounding potential mechanisms for TTS has recently been reviewed (9). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been made in recipients of the Janssen HAdV-D26.COV2.S vaccine, derived from the species D human adenovirus type 26 (HAdV-D26) ( 5 , 7 ). The pathological mechanism underpinning TTS is unknown, although recent reports highlight a probable role for platelet factor 4 (PF4) ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after receiving conditional marketing authorization in Europe, cases of thrombotic thrombocytopenia were observed, an unusual and, if untreated, often fatal syndrome of thrombosis of the cerebral venous sinuses and other large vessels together with low platelet counts. Occurring between 5 and 28 days after vaccination ( Othman et al, 2021 ), this syndrome, now coined vaccine-induced immune thrombotic thrombocytopenia (VITT) or thrombosis with thrombocytopenia syndrome, and related to autoimmune heparin-induced thrombocytopenia ( Greinacher et al, 2017 ), was found to be linked to vaccination with ChAdOx1 ( Paul-Ehrlich-Institut, 2021 ), and has been described to be mediated by platelet-activating antibodies against platelet factor 4 (PF4) ( Greinacher et al, 2021a ; Greinacher et al, 2021b ; Pavord et al, 2021 ; Schultz et al, 2021 ; Scully et al, 2021 ; Tiede et al, 2021 ; Wolf et al, 2021 ). Also Ad26.COV2.S has been linked to VITT ( Muir et al, 2021 ; Paul-Ehrlich-Institut, 2021 ), however at a lower frequency ( Paul-Ehrlich-Institut, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the electrostatic nature of the adenovirus capsid coupled with shape complementarity provides an opportunity for the adenovirus to cluster PF4, potentially creating neoantigens, which trigger the production of anti-PF4 from memory B-cells. 24,25 This 'clustering' of PF4 on the adenovirus capsid appears to occur primarily at the interface between the major capsid protein (hexon), and appears to be a relatively low affinity (∼300 -600 nM) and largely electrostatic interaction.…”
Section: Immunogenicity In Vittmentioning
confidence: 99%